Tindak Pidana Pengangkutan Batu Hitam Secara Ilegal - Difa Mauizhah Aulia Tayeb; Lisnawaty W Badu; Nuvazria Achir (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research discusses the causes of the crime of transporting black stone in the jurisdiction of the Gorontalo Regional Police and efforts to overcome it. The method used in the research is empirical with qualitative descriptive data analysis which describes and describes data and field facts. Based on research results, Gorontalo is in 5th position in the province with the highest poverty; and The lack of public understanding and knowledge regarding mining, where the lack of public knowledge, influences the existence of illegal mining. This situation is based on a lack of education and understanding as the main factors in the community's decision to carry out illegal mining actions, including a lack of socialization and legal education to the community. The prevention of criminal acts of transporting black stone by the Gorontalo Regional Police is carried out through initial efforts made by the police, in this case the Gorontalo Regional Police, namely visiting or visiting the community and providing advice regarding mining activities. Apart from that, conduct patrols in mining areas for early handling, especially checking permits for heavy vehicles used in mining areas, including transport vehicles. Not only that, legal counseling and socialization is also carried out to the community as a first step in overcoming this criminal act; and Repressive Efforts by taking action against the perpetrators, in order to have a deterrent effect. This step is carried out through investigations, inquiries and other coercive measures authorized by law, which end with the application of criminal sanctions against the perpetrators.